Provision for Sanitary Epidemiological Welfare of the Population of the Jewish Autonomous Region during High Water and Post-Flooding Period - V. A. Yanovich; O. N. Nikulina; E. S. Mironenko; O. A. Ishutkina; V. V. Chaban; I. S. Butenko; P. V. Kopylov; Yu. G. Beznogov; I. P. Snetkova; L. Yu. Malekhanova (Проблемы особо опасных инфекций, 2014)
Put forward was operational protocol as regards Rospotrebnadzor institutions policies in the territory of the Jewish Autonomous Region for the prevention of epidemiological implications during the post-flooding period in reference to infectious diseases. Carried out were control measures over infection morbidity rate, drinking water quality, disinfection of water supply sources, as well as sewage systems. Actions undertaken made it possible to prevent cluster cases of infectious diseases both in the flooded areas and at the temporal accommodation sites; to provide control over acute intestinal and natural-focal disease incidence, keeping it to the level of long-term average annual indexes; and to supply the population with drinking water of high quality.